1996
DOI: 10.1007/bf01857606
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the relation between tnterview-derived hostility scores and resting blood pressure

Abstract: We examined the correlations between Structured Interview (SI)-derived hostility scores and resting blood pressure (BP) to see if they would be the same or different for healthy men and women. Standard risk factor information and resting BP measures were obtained from 193 undergraduates (109 men, 84 women), who underwent the SI. Subjects were rated for Potential for Hostility, Hostile Style, Intensity and Content, and completed Antagonism and Neuroticism scales. As expected, SI hostility scores were related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This finding suggests that the use of denial may involve more cognitive work for men than for women. Also, a gender-based differential relation of DBP to a personality variable has been reported by Davidson, Hall, and MacGregor (1996), who found both DBP and SBP to be predicted by an interaction between gender and an index of hostility. Subsequent testing indicated that hostility predicted higher SBP for men, but lower SBP for women.…”
Section: Discussionmentioning
confidence: 69%
“…This finding suggests that the use of denial may involve more cognitive work for men than for women. Also, a gender-based differential relation of DBP to a personality variable has been reported by Davidson, Hall, and MacGregor (1996), who found both DBP and SBP to be predicted by an interaction between gender and an index of hostility. Subsequent testing indicated that hostility predicted higher SBP for men, but lower SBP for women.…”
Section: Discussionmentioning
confidence: 69%
“…Research about gender differences in hostility expression is essential both because previous research has proposed that gender stereotypes exist and because former studies have failed to review the existence of a potential gender bias when examining the observation and rating of hostility (Davidson, Hall, & MacGregor, 1996). Of the different kinds of hostility expression, verbal and nonverbal/behavioral hostility are both easily amenable to observation and are seen as more characteristic of women and men, respectively.…”
Section: Discussionmentioning
confidence: 99%